Conhecimento, atitude e prática de pacientes frente aos métodos de rastreamento do câncer de mama - Sara Dalia Barbosa (2007)
The present study aims to determine the knowledge, attitude and practice of the breast cancer screening methods among the users of the public care service in Belo Horizonte. A KAP study questionnaire surveying a sample of 236 women, throughout the county healthcenters. The sample was calculated using Cochrans formula. The 2 test was calculated to compare the two groups, adequate and inadequate, according to the control variables. The results revealed an inadequacy of knowledge, attitude and practice among users of thepublic health care, in respect to Breast Self Examination, Clinical Examination and Mammograph.